A Combination of Outcome and Process Feedback Enhances Performance in Simulations of Child Sexual Abuse Interviews Using Avatars - Pompedda, Francesco; Antfolk, Jan; Zappalà, Angelo; Santtila, Pekka (Frontiers in Psychology, 2017)
Simulated interviews in alleged child sexual abuse (CSA) cases with computer-generated avatars paired with feedback improve interview quality. In the current study, we aimed to understand better the effect of different types of feedback in this context. Feedback was divided into feedback regarding conclusions about what happened to the avatar (outcome feedback) and feedback regarding the appropriateness of question-types used by the interviewer (process feedback). Forty-eight participants each interviewed four different avatars. Participants were divided into four groups (no feedback, outcome feedback, process feedback, and a combination of both feedback types). Compared to the control group, interview quality was generally improved in all the feedback groups on all outcome variables included. Combined feedback produced the strongest effect on increasing recommended questions and correct conclusions. For relevant and neutral details elicited by the interviewers, no statistically significant differences were found between feedback types. For wrong details, the combination of feedback produced the strongest effect, but this did not differ from the other two feedback groups. Nevertheless, process feedback produced a better result compared to outcome feedback. The present study replicated previous findings regarding the effect of feedback in improving interview quality, and provided new knowledge on feedback characteristics that maximize training effects. A combination of process and outcome feedback showed the strongest effect in enhancing training in simulated CSA interviews. Further research is, however, needed.